Intraoperative changes in blood pressure associated with cerebral desaturation in infants. Issue 7 (30th April 2015) - Michelet, Daphné; Arslan, Ozkan; Hilly, Julie; Mangalsuren, Nyamjargal; Brasher, Christopher; Grace, Robert; Bonnard, Arnaud; Malbezin, Serge; Nivoche, Yves; Dahmani, Souhayl; Anderson, Brian
Summary Background Intraoperative hypotension has been linked to poor postoperative neurological outcomes. However, the definition of hypotension remains controversial in children. We sought to determine arterial blood pressure threshold values associated with cerebral desaturation in infants. Methods After ethics committee approval, infants younger than 3 months were included in this prospective observational study. Cerebral saturation was assessed using near‐infrared spectroscopy. The primary goal of the study was to determine percentage reductions in intraoperative systolic blood pressure (SBP) and mean blood pressure (MBP) associated with decreases in cerebral blood oxygen saturation of >20%, when compared to baseline. Analyses were performed using a bootstrap receiving operator characteristic (ROC) curves with determination of the gray zone. Results Sixty patients were recruited and 960 measurement points were recorded. Fifty‐nine data points (6.1%) recorded cerebral desaturation of >20% when compared to baseline. The areas under the ROC curves were 0.79 (0.74–0.84) and 0.67 (0.6–0.75) for percentage decreases in SBP and MBP, respectively. Gray zone values with false‐positive and negative rates <10% were SBP decreases of 20.5% and 37.5%, respectively, and MBP decreases of 15.5% and 44.5%, respectively. Conclusion Our results indicate that falls in noninvasive systolic blood pressure of <20% from baseline are associated with a <10% chance of cerebral desaturation in neonates and infants <3 months of age undergoing noncardiac surgery. As such, maintaining systolic blood pressure above this threshold value appears a valid clinical target.